Dimensions of Language Anxiety in Students’ Speaking Skills and Strategies for Overcoming It: A Case Study of Students in the Arabic Language Education Program in Riau Province - Arik Maghfirotul Mukarom; Uril Bahruddin; Abdul Aziz (Asalibuna, 2025)
This study aims to analyze the dimensions of language anxiety in students’ speaking skills in the Arabic Language Education Department in Riau Province, to identify the factors contributing to the emergence of such anxiety, and to explore the strategies employed by students to cope with it. This study adopts a qualitative approach using a case study design. Data were collected through interviews, observations, and document analysis, and subsequently analyzed using thematic analysis. The findings indicate that language anxiety in speaking skills is multidimensional in nature, manifested in three main dimensions: the linguistic anxiety dimension, the psychological anxiety dimension, and the situational anxiety dimension. The linguistic dimension is associated with concerns about grammatical errors, limited vocabulary, and pronunciation difficulties. The psychological dimension relates to affective factors, such as feelings of embarrassment, fear of negative social evaluation, and low self-confidence. Meanwhile, the situational dimension is linked to learning situations influenced by instructional contexts, particularly in formal and evaluative settings such as presentations and oral examinations. The study also reveals that students employ a variety of cognitive, affective, and social strategies to cope with language anxiety in speaking performance, although the effectiveness of these strategies largely depends on the level of support provided by the pedagogical environment. The study concludes that language anxiety in speaking skills cannot be understood merely as an issue of linguistic competence, but rather as a complex learning phenomenon. Furthermore, this study offers a conceptual framework grounded in students’ experiences to understand the dimensions of anxiety within the context of Arabic language education at the university level. Therefore, the teaching of speaking skills should be designed using an approach that is more sensitive to students’ affective conditions, as this approach plays a crucial role in enhancing self-confidence and increasing student participation in the learning process.   ملخص تهدف هذه الدراسة إلى تحليل أبعاد القلق اللغوي في مهارة الكلام لدى طلبة قسم تعليم اللغة العربية في محافظة رياو، وتحديد العوامل المؤثرة في ظهور هذا القلق، وإلى استكشاف استراتيجيات الطلبة المستخدمة للتغلب على هذا القلق. تعتمد هذه الدراسة على المنهج النوعي باستخدام تصميم دراسة حالة. وتم جمع البيانات من خلال المقابلات، وملاحظة، والوثائق. ثم جرى تحليلها باستخدام التحليل الموضوعي. وتشير نتائج الدراسة إلى أن القلق اللغوي في مهارة الكلام يتسم بطابع متعدد الأبعاد، ويتجلى ذلك في ثلاثة أبعاد رئيسة، هي البعد اللغوي للقلق، والبعد النفسي للقلق، والبعد الموقفي للقلق. ويرتبط البعد اللغوي للقلق بالخشية من الأخطاء في البنية اللغوية، ومحدودية المفردات، وصعوبات النطق. وأما البعد النفسي للقلق فيتعلق بالمشاعر، مثل الشعور بالخجل، والخوف من التقييم الاجتماعي السلبي، وانخفاض مستوى الثقة بالنفس. ويرتبط البعد الموقفي للقلق بالمواقف التي تتأثر بسياق التعلم، ولا سيما في الحالات الرسمية والتقويمية، مثل العروض التقديمية والاختبارات الشفوية. واستكشفت هذه الدراسة أن الطلبة يستخدمون مجموعة متنوعة من الاستراتيجيات المعرفية والاستراتيجيات الوجدانية والاستراتيجيات الاجتماعية للتغلب على القلق اللغوي في أداء مهارة الكلام، على الرغم من أن فاعلية هذه الاستراتيجيات تعتمد إلى حدّ كبير على مستوى الدعم الذي توفره البيئة البيداغوجية. وتخلص هذه الدراسة إلى أن القلق اللغوي في مهارة الكلام لا يمكن فهمه بوصفه مجرد مسألة تتعلق بالقدرة اللغوية فحسب، بل يعدّ ظاهرة تعلمية معقدة. كما تقدم الدراسة في الوقت ذاته إطارا تصوريا قائما على خبرات الطلبة لفهم أبعاد القلق في سياق تعليم اللغة العربية في المرجلة الجامعية. ولذلك، ينبغي أن يصمّم تعليم مهارة الكلام وفق مقاربة أكثر حساسية تجاه الظروف الوجدانية لدى الطلبة. وتكتسب هذه المقاربة أهمية بالغة في تعزيز مستوى الثقة بالنفس وزيادة مشاركة الطلبة في عملية التعلم.